2009
DOI: 10.1007/s10344-009-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

Key landscape factors for Eurasian otter Lutra lutra visiting rates and fish loss in estuarine fish farms

Abstract: Conflicts between the conservation of large vertebrates and the use of biological resources are common and affect many species and activities. The vast majority of the Portuguese fish farms are located in estuarine protected areas and production of marine fish species is done mostly in semi-intensive regimes and with the imposition of some restrictive rules. This exposed form of production is prone to predation by wild animals. The Eurasian otter Lutra lutra is widely distributed in Portugal and this combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Shellfish farms also increase local abundance of generalist or molluscivorous 489 bird functional groups (Roycroft et al 2004;Kirk et al 2007), but others, such as 490 invertivorous wading birds, may be displaced by shellfish farm infrastructure or associated 491 ecological changes (Kelly et al 1996;Godet et al 2009;Broyer & Calenge 2010). and estuarine sea cages in Europe Sales-Luis et al 2009), but our search 502 did not reveal any data on abundance or attraction to farms relative to natural waterways. Our meta-analysis indicated that farm-associated fish tend to be larger and heavier, a finding 509 that is consistent with either aggregation of adult fish or higher growth rates due to a trophic 510 subsidy.…”
mentioning
confidence: 84%
“…Shellfish farms also increase local abundance of generalist or molluscivorous 489 bird functional groups (Roycroft et al 2004;Kirk et al 2007), but others, such as 490 invertivorous wading birds, may be displaced by shellfish farm infrastructure or associated 491 ecological changes (Kelly et al 1996;Godet et al 2009;Broyer & Calenge 2010). and estuarine sea cages in Europe Sales-Luis et al 2009), but our search 502 did not reveal any data on abundance or attraction to farms relative to natural waterways. Our meta-analysis indicated that farm-associated fish tend to be larger and heavier, a finding 509 that is consistent with either aggregation of adult fish or higher growth rates due to a trophic 510 subsidy.…”
mentioning
confidence: 84%
“…In Lithuania, various companies, state fish hatcheries and farmers engaged in fish farming own more than 12,000 ha of ponds (Pečiukėnas 2006;Baltrūnaitė, unpubl.). The diet of the otter (Kortan et al 2007;Ludwig et al 2002;Lanszki et al 2007;Marques et al 2007;Georgiev 2008), damage extent (Kranz 2000;Kloskowski 2005a, b;Wísniows-ka 2006), predator -human conflicts and their solution mechanisms (Myšiak et al 2004;Freitas et al 2007;Schwerdtner & Gruber 2007;Sales-Luís et al 2009) are now widely discussed in many studies. There is no data on the otter diet in fish farms in Lithuania.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence-based knowledge concerning habitat requirements of the otter and habitat characteristics driving spatiotemporal variability of its population is crucial for effective conservation of the species. Moreover, bearing in mind potential otter–human interaction and conflicts in the context of fishery production (e.g., Sales-Luis et al 2009; Kloskowski 2011), data on habitat correlates of the Eurasian otter are needed for proper population management of this species. The aim of this study was to examine the Eurasian otter population trends and to assess habitat correlates explaining occurrence of the species in Central Poland along two decades.…”
Section: Introductionmentioning
confidence: 99%